Risk-Based Highest and Best Use (HBU) Analysis of Asset Utilization Operations Cooperation Business Model - Putra, Agung Andrian (Eduvest - Journal of Universal Studies, 2025)
This study addresses the challenge of optimizing the utilization of Dutch colonial heritage buildings in Indonesia, focusing on the Philately Building owned by PT Pos Indonesia (Persero). The research problem revolves around identifying an ideal business model for asset utilization through operational cooperation (KSO) while assessing investment feasibility and risk mitigation. The objectives are to analyze the optimal business model and evaluate the financial and operational viability of repurposing the building for cultural, culinary, or integrated tourism. A mixed-methods approach was employed, combining qualitative data from interviews, documentation, and observations with quantitative financial analysis (NPV, IRR, Payback Period). The Highest and Best Use (HBU) framework was applied to evaluate legal, physical, and financial aspects, alongside risk analysis using root cause assessment. Findings reveal that an integrated tourism model, combining cultural preservation, entertainment, and recreation, is the most financially viable option, with an IRR of 16.7% and a payback period of 8.14 years. The KSO model emerged as optimal, enabling risk-sharing, professional management, and diversified revenue streams while preserving historical value. Key risks include regulatory compliance and operational challenges, mitigated through detailed planning and partnerships. The research implications highlight the importance of HBU analysis in decision-making for heritage asset utilization, offering a replicable framework for similar projects. Practically, it provides PT Pos Indonesia and other stakeholders with actionable insights to balance preservation and profitability, fostering sustainable development of cultural heritage assets.